Real Exchange Rate and Economic Growth: An Empirical Assessment for Vietnam - Huong, DO Thi My (Asian Economic and Financial Review, 2019)
In theory, exchange rates and economic growth are regarded as having an indirect link via trade and capital investment. However, empirical investigation of this link in the context of one specific country has not hitherto been seriously considered, and Vietnam is no exception. It is essential that policy makers have insight into the extent to which exchange rates impact on their country’s rate of economic growth. This paper aims to do so for Vietnam. By conducting a Vector autoregression (VaR) estimation, the Granger Causality test, and impulse response, the article aims to analyze empirically the effects of real exchange rates on economic growth in Vietnam from 2007 to 2017 using quarterly data. The results show a positive relationship between real exchange rates and economic growth. A one percentage point real depreciation in Vietnamese dong rates (VND) may lead to a 1.61923 percent growth in real gross domestic product (GDP) in this country, but this takes effect only during the first four periods (or lag 1). Moreover, The variance decomposition of forecast errors (FEVD) outcome also reveals that the real effective exchange rate (REER) made only a small contribution to GDP growth over the decade to 2017 compared to earlier periods.